Credit Pages from an Accounting Ledger, a Fair Copies of the Borges Tales from 1939 to 1941 - Balderston, Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article focuses on Borges’s practice of writing the second drafts of most of the stories in The Garden of Forking Paths, the book published in 1941, in Credit pages from an accounting ledger. After reconstructing the contents of this ledger (which was dismembered after being used), the draft of “Examination of the Work of Herbert Quain.” From detailed examination of differences between this manuscript and the version published in Sur, it is possible to date this version with some precision.